Raising Public Awareness of the Impact of Divorce on Children - Firli Adila Sari; Zahwa Abida Fiska; Aldi Firman Saputra; Yohanes Bona Arga (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Parental divorce is a complex issue that has a significant impact on children, both from a psychological, social and educational perspective. This research analyzes the impact of divorce on children, focusing on psychological, social and educational aspects. Through literature studies from various sources, this research found that divorce can cause children to experience emotional trauma, adjustment difficulties, behavioral problems, learning difficulties, and decreased achievement. Children who are victims of divorce are also vulnerable to mental problems, such as low self-esteem, easily giving up hope, apathy, and even criminal acts. This research emphasizes the important role of parents, teachers, social workers and the government in providing support and protection to children who are victims of divorce. The importance of public awareness about the impact of divorce on children was also emphasized.